2000
DOI: 10.1017/s1368980000000021
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of body weight in the Baltic Republics

Abstract: Objective: Previously recorded rates of obesity in the Baltic Republics have been among the highest in the world although little is known about how they vary within the population. This study investigates the distribution of body mass index (BMI) and obesity in these countries. Design: Three cross-sectional surveys conducted in the summer of 1997. Setting: Estonia, Latvia and Lithuania. Subjects: Representative national samples of adults with measured weight and height (Estonia: n = 1154; Latvia: n = 2292; Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 15 publications
3
18
1
Order By: Relevance
“…Among the socio-economic and lifestyle factors examined in this study, only educational achievement and alcohol intake were significantly associated with the likelihood of being obese, and this only in women. In accordance with findings from other investigators 36,43 , there was a tendency for women with a lower education level to be more likely to be obese compared with those with a higher level of education. The lack of consistent relationship with standard socio-economic factors in this study (including with income -an observation also reported from surveys conducted in the Baltic countries 35 ) could be due to the dislocation of income and other measures of social status in a society such as Albania that has undergone a massive transformation in a very short time, making these constructs less relevant as determinants of behaviour 44 .…”
Section: Discussionsupporting
confidence: 92%
“…Among the socio-economic and lifestyle factors examined in this study, only educational achievement and alcohol intake were significantly associated with the likelihood of being obese, and this only in women. In accordance with findings from other investigators 36,43 , there was a tendency for women with a lower education level to be more likely to be obese compared with those with a higher level of education. The lack of consistent relationship with standard socio-economic factors in this study (including with income -an observation also reported from surveys conducted in the Baltic countries 35 ) could be due to the dislocation of income and other measures of social status in a society such as Albania that has undergone a massive transformation in a very short time, making these constructs less relevant as determinants of behaviour 44 .…”
Section: Discussionsupporting
confidence: 92%
“…We expect individual weight (and BMI) to increase with age, at least up to middle age, but eventually metabolism declines and the digestive system starts to lose its efficiency (Kaufmann, 2006). The study by Pomerleau et al (2000) show that the BMI in the Baltic countries increases with age and Abdulai (2005) finds a positive but concave relationship between age and BMI in Ghana. Therefore, we expect g 10 > 0 and g 11 < 0.…”
Section: Methodsmentioning
confidence: 97%
“…In a national sample investigated in 1997, the prevalence of obesity among 20-to 34-year-old Lithuanians was 6% for both sexes but the prevalence of overweight was higher in men than in women, 34 and 19%, respectively, while 8% of women but no men were underweight (27). Thus, these differences in the prevalence of overweight are consistent with our findings of a greater increase of diabetes incidence in men compared with women in the corresponding age-groups.…”
Section: Incidence According To Age and Sexmentioning
confidence: 98%